Comparative Transcriptome and Metabolome Profiling Revealed Molecular Cascade Events During the Enzymatic Browning of Potato Tubers After Cutting - Wang, Li; Shan, Jianwei; Liu, Jitao; An, Kang; Yang, Kun; Li, Chengchen; Li, Xiaobo; Xiong, Xingyao (Plants (Basel), 2025)
Enzymatic browning is a major issue in potato processing, causing a decline in both nutritional value and quality. Although there are numerous studies on the mechanism of enzymatic browning of potato tubers, few relevant reports are available on the changes at the transcriptome level during enzymatic browning as well as on the differences in the browning process of potato tubers with differing degrees of enzymatic browning potential. To gain insights into the molecular mechanism of enzymatic browning after cutting, this study presents the transcriptional characterization of temporal molecular events during enzymatic browning of browning-resistant (BR) and browning-susceptible (BS) potato tubers. RNA-sequencing (RNA-seq) analysis detected 19,377 and 13,741 differentially expressed genes (DEGs) in BR and BS tubers, respectively, with similar function enrichment observed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Up-regulated DEGs were significantly enriched in the pathways related to phenol and lipid biosynthesis, while the down-regulated DEGs were significantly enriched in the pathways related to programmed cell death. Significant redox-related pathways occurred earlier in BS tubers compared to the BR tubers. Further analysis revealed that the BS tubers had a stronger phenolic synthesis ability compared to the BR tubers. However, the BR tubers showed a stronger free radical scavenging ability compared to the BS tubers. The results of our study provide insights into the temporal molecular events that occur during the enzymatic browning of potato tubers after cutting and the potential molecular mechanisms for different degrees of enzymatic browning.